2019
DOI: 10.1111/jtxs.12458
|View full text |Cite
|
Sign up to set email alerts
|

Shear and extensional rheology of acid milk gel suspensions with varying ropiness

Abstract: Exopolysaccharides (EPS) synthesized by lactic acid bacteria during fermentation significantly affect the rheology of set‐style acid milk gels and that of acid gel suspensions, produced from the gels by stirring. In this study, shear and uniaxial extensional flow of acid gel suspensions made with seven single strains of Streptococcus thermophilus or Lactococcus lactis was investigated. Six strains produced ropy EPS, and maximum filament length determined by using a continuous stretching method was up to four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In similar research, Surber et al (2020) observed that milk fermented with the EPSproducing strain NCC1971 exhibited higher shear stress compared to milk fermented with the non-EPS-producing strain NCC2201 [41]. The shear stress of milk fermented with NCC1971 increased to a plateau around 70 Pa after reaching a maximum shear rate of 186 s −1 , attributed to the resistance of EPS-bacterial cell bonds breaking under maximum treatment.…”
Section: Apparent Viscosity and Resistance To Shearingmentioning
confidence: 90%
“…In similar research, Surber et al (2020) observed that milk fermented with the EPSproducing strain NCC1971 exhibited higher shear stress compared to milk fermented with the non-EPS-producing strain NCC2201 [41]. The shear stress of milk fermented with NCC1971 increased to a plateau around 70 Pa after reaching a maximum shear rate of 186 s −1 , attributed to the resistance of EPS-bacterial cell bonds breaking under maximum treatment.…”
Section: Apparent Viscosity and Resistance To Shearingmentioning
confidence: 90%
“…With two simple example experiments, we have highlighted the need for high-speed imaging in capillary breakup extensional rheometry rather than using a laser micrometer with a finite thickness as many previous studies have done [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In experiments, the filament-thinning evolution is typically tracked using a laser micrometer [6][7][8][9][10][11][12][13][14][15][16][17][18][19] (such as that originally equipped on the commercial HAAKE™ CaBER™ 1 device) or high-speed imaging techniques. Typically, the laser micrometer has a finite thickness h micro = O(1 mm) and, in the case of the commercial HAAKE™ CaBER™ 1 device, its axial location is fixed, and it is the position of the end-plates that is adjusted to ensure that the laser micrometer is located at the axial location of filament breakup.…”
Section: Introductionmentioning
confidence: 99%
“…The growing demand for fat-free foods due to new eating habits on the consumers creates problems related to the consistency of yoghurts, presenting an unstable and more fragile structure, which can lead to sensory rejection (Steffe, 1996;Surber, Jaros, & Rohm, 2019). However, optimization studies applied to yoghurts are rarely found (Granato et al, 2010;Popović et al, 2013;Pakseresht et al, 2017) and there are no studies related to optimization of the texture profile and rheological characteristics of yogurt supplemented with transglutaminase.…”
Section: Introductionmentioning
confidence: 99%